Seleção recorrente visando resistência à mancha angular no feijoeiro com inoculação artificial precoce - Librelon, Samira Santiago (2016)
The Federal University of Lavras - UFLA in partnership with Embrapa has been conducted a common bean breeding program for resistance to Pseudocercospora griseola using recurrent selection method since 1998. The selection has been carried out in the field at the time of high natural occurrence of the pathogen, therefore, a cycle has conducted per year. The efficiency of artificial inoculation of P.griseola and early evaluation of severity of angular leaf spot in common bean progenies of this program were evaluated. For this, 254 and 166 S 0:1 progenies from cycles XVI and XVIII, respectively, were evaluated. Progenies of both cycles were evaluated for severity of blight in the field, with the natural occurrence of pathogen, and in greenhouse with artificial inoculation of P. griseola. Grain yield in the trials was also evaluated. Obtained data were submitted to analysis of individual and combined variance. Genetic and phenotypic parameters were estimated for angular leaf spot severity, as well as the coincidence of the evaluations carried out in the field and in the greenhouse. All progenies showed high level of resistance to angular leaf spot, indicating the efficiency of recurrent selection. Artificial inoculation of P.griseola in the greenhouse showed promise for the selection of resistant plants in a recurrent selection program allowing to carry out two cycles per year. To optimize the use of recurrent selection, it was proposed a scheme combining the advantages of early selection with artificial inoculation of pathogen in the greenhouse with the advantages of selection in the field with natural occurrence of P. griseola in the dry season.